Estimation of the Operating Force From the Human Motion - Ming Ding; Baba, Ryuzo; Masanthia, Kristada; Garcia Ricardez, Gustavo Alfonso; Takamatsu, Jun; Ogasawara, Tsukasa (Conference proceedings (IEEE Engineering in Medicine and Biology Society. Conf.), 2018)
In this research, we propose a new method to estimate the operating force exerted when moving an object with the hands by observing the human motion only. The required force for moving the object can be estimated without equipping any sensors on the object or on the human body. From the measured joint angles, we calculate the center of mass and the hand's position using a human model. Then, the operating forces of the hands can be estimated by considering the balance of forces and moments using a dynamic model. In the experiments, we estimated the operating force of the hands for three representative movements of operating a box: pushing, pulling and lifting. By comparing the estimated and measured operating force, we verified the effectiveness of the proposed method with human subjects.